2022
DOI: 10.1155/2022/9433225
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Apically Extruded Debris during Pulpectomy Procedure in Primary Molar Teeth Using Two Different Rotary Systems and Hand Files: An In Vitro Study

Abstract: Background. Successful outcome of endodontic treatment depends on chemomechanical preparation of the tooth. However, during canal preparation, debris may extrude through the apical foramen causing postoperative complications. The aim of this study is to evaluate and compare the amount of apically extruded debris during the pulpectomy procedure in primary molar teeth using two different rotary files and hand files. Materials and Methods. Distal roots of sixty extracted primary molars were divided into three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
2
0
0
1
Order By: Relevance
“…Apical extrusion of debris is an inherent side effect during the process of root canal preparation. All the instrumentation techniques were found to be associated with apical debris extrusion in this study, which aligns with previous investigations [ 20 22 ]. The quantity of extruded debris is subject to variation depending on the design and kinematics of the instrument [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…Apical extrusion of debris is an inherent side effect during the process of root canal preparation. All the instrumentation techniques were found to be associated with apical debris extrusion in this study, which aligns with previous investigations [ 20 22 ]. The quantity of extruded debris is subject to variation depending on the design and kinematics of the instrument [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is in the line with that of Nanavati et al [15] who found that throughout pulpectomy, pediatric rotary files extruded considerably less quantity of apical debris than manual files when measuring apically extruded debris of distal roots of 60 primary lower molar teeth by utilizing two types of rotary files and hand files, namely, Prime Pedo™ pediatric rotary files, DXL-Pro Pedo™ pediatric rotary files, and hand K-files.…”
Section: Discussionsupporting
confidence: 92%
“…5 Apikalden taşan debris miktarını araştıran çalışmalar, tüm kanal şekillendirme tekniklerinin ve eğelerinin debris taşmasına neden olduğunu bildirmiştir. [6][7][8] Resiprokasyon ve devamlı rotasyonla çalışan eğe sistemlerinin apikalden taşan debris miktarı üzerine etkisi hakkında literatürde farklı sonuçlar bulunmaktadır. Bürklein ve Schäfer 9 , tam devamlı rotasyonla çalışan Mtwo (VDW, Münih, Almanya) ve ProTaper (Dentsply Maillefer, Ballaigues, İsviçre) eğelerinin kullanıldığı çoklu eğeli sistemlerle yapılan kök kanal şekillendirmesinin, resiprokasyon hareketiyle çalışan tek eğe sistemleri olan Reciproc (VDW) ve WaveOne (Dentsply Sirona) kullanımına kıyasla daha az debris taşmasına sebep olduğunu bildirmiştir.…”
Section: şEkilunclassified